Precocious Puberty or Premature Thelarche: Analysis of a Large Patient Series in a Single Tertiary Center with Special Emphasis on 6- to 8-Year-Old Girls - Varimo, Tero; Huttunen, Heta; Miettinen, Päivi Johanna; Kariola, Laura; Hietamäki, Johanna; Tarkkanen, Annika; Hero, Matti; Raivio, Taneli (Frontiers in Endocrinology, 2017)
Introduction: We describe the etiology, MRI findings, and growth patterns in girls who had presented with signs of precocious puberty (PP), i.e. premature breast development or early menarche. Special attention was paid to the diagnostic findings in 6 to 8 year-olds. Material and methods: We reviewed the medical records of 149 girls (aged 0.7 to 10.3 years) who had been evaluated for PP in the Helsinki University Hospital between 2001 and 2014. ¨ Results: In 6 to 8 year-old-girls, PP was most frequently caused by idiopathic GnRH-dependent PP (60%) and premature thelarche (PT; 39%). The former subgroup grew faster (8.7 ± 2.0 cm/yr, n=58) than the girls with PT (7.0 ± 1.1 cm/yr, n=32) (P < 0.001), and the best discrimination for GnRH-dependent PP was achieved with a growth velocity cut-off value of 7.0 cm/yr (sensitivity 92% and specificity 58%) (AUC 0.82, 95% CI; 0.73-0.91, P < 0.001). Among asymptomatic and previously healthy 6 to 8-year-old girls with GnRH-dependent PP, one (1.7%, 95% CI; 0.3-9.7%), had a pathological brain MRI finding requiring surgical intervention (craniopharyngioma). In girls younger than 3 years, the most frequent cause of breast development was PT, and, in 3 to 6-year-olds, GnRH-dependent PP. Conclusions: In 6 to 8 year-old-girls, analysis of growth velocity is helpful in differentiating between PT and GnRH-dependent PP. Although the frequency of clinically relevant intracranial findings in previously healthy, asymptomatic 6 to 8-year-old girls was low, they can present without any signs or symptoms, which favors routine MRI imaging also in this age group.